Entrapment of chromium in cement with waste material. (2021) - Biswal, Sudhansu Sekhar; Panda, Chittaranjan; Sahoo, Sudarsan; Jena, Trilochan
Abstract: Cr (VI) is found to be the most mobile chromium form in water systems and is very toxic to biological system. That is why there are stringent standards for chromium in wastewater i.e. 0.1 mg/l for Cr (VI) and 2.0 mg/l for total chromium for discharge to inland surface water in India. Cement matrix very often provides effective binders for immobilization of toxic heavy metals like chromium. Here in this work, five different pastes were made from cement with waste material by using Portland cement and blended cements with slag, fly ash, like electric arc furnace (EAF) dust and sponge iron kiln dust were prepared. The paste samples were subjected to toxicity characteristic leaching procedure (TCLP) at pH 2.88 with wastewater of different concentrations of Cr (VI) and with different water to binder ratio. The leaching process from these pastes indicate that Cr (VI) compounds were not entrapped properly in ordinary Portland cement and fly ash based cement, whereas blended cement paste with blast furnace slag, electric arc furnace dust and sponge iron kiln dust provide the satisfactory immobilization medium. The TCLP test results indicate that leachate chromium values are well within the required norm. It also complies the requirement of wastewater discharge standard for chromium by government of India.